National Conference on Creativity in Education & Humanities 2017: Empowering People (NCC2017) - PPIK, Pusat Pengajian Ilmu Kemanusiaan; HCC, Han Chiang College; SUNU, Sunway University (2017)
We are very pleased to announce that the National Higher Education Research Institute (IPPTN) and the School of Humanities, Universiti Sains Malaysia in collaboration with Sunway University, Han Chiang College and USAINS Holding Sdn. Bhd. will be organising the National Conference on Creativity in Education & Humanities 2017: Empowering People (NCC2017)as per details below: